Manejo integrado de plagas en tomate fase III: 1993-1994 - Rufino Salazar, J.; Trabanino, E.; Landaverri, E.; Medina, J.A.; Ibarra, M. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Proyecto MIP-ICTA-CATIE-ARF, Guatemala (Guatemala), 2014)
Ilus. Tab. 2 ref.